2020
DOI: 10.4102/sajhivmed.v21i1.970
|View full text |Cite
|
Sign up to set email alerts
|

Empowering parents for human immunodeficiency virus prevention: Health and sex education at home

Abstract: Background: Improving health literacy amongst human immunodeficiency virus (HIV)-positive mothers could strengthen child and adolescent HIV prevention. The Amagugu intervention included health literacy materials to strengthen maternal communication and has demonstrated success in low-resource HIV-endemic settings.Objectives: Our aims were to (1) evaluate whether Amagugu materials improved health literacy leading to changes in parental behaviour towards communicating on topics such as HIV, health behaviours and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This perpetuates poor communication cycles, entrenches traditional social norms concerning adolescents' and young people's sexuality, and affects adults' perceived self-confidence. In this study., a perceived lack of capacity, including the skills and ability to overcome fears and embarrassment were barriers to honest conversations about SRH (Edwards et al 2020). Gender norms that suggest that these discussions should be facilitated by a parent or caregiver of the same gender may also mean that some caregivers feel unable to have conversations with children or young people of the opposite sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This perpetuates poor communication cycles, entrenches traditional social norms concerning adolescents' and young people's sexuality, and affects adults' perceived self-confidence. In this study., a perceived lack of capacity, including the skills and ability to overcome fears and embarrassment were barriers to honest conversations about SRH (Edwards et al 2020). Gender norms that suggest that these discussions should be facilitated by a parent or caregiver of the same gender may also mean that some caregivers feel unable to have conversations with children or young people of the opposite sex.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding discomfort associated with caregiver sex/gender could be alleviated by leveraging traditional norms, particularly related to raising children communally with other family or community members identified to fulfil the task (Bhana, Crewe, and Aggleton 2019). These positive interactions could lead to changes in how adolescents and young people engage with their own children one day (Edwards et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Effecting health behaviour change through acceptable instructional material like a storybook was a topic of previous studies (Agustina et al, 2018;Conrad et al, 2020;Edwards et al, 2020;Harrison et al, 2016;Kalembo et al, 2019;Pulimeno et al, 2020). Particularly, the works of Kalembo et al (2019) and Edwards et al (2020) highlighted the significance of using the mother tongue in producing health literacy material.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown that healthcare professionals have used children's stories for therapeutic purposes, precluding harmful behaviours and addictions or dealing with psychosomatic disorders (Pulimeno et al, 2020). It has been used to change health behaviours related to human immunodeficiency virus (HIV) status (Edwards et al, 2020;Kalembo et al, 2019); overweight and disability (Harrison et al, 2016); eating and physical activity behaviours (Bellows et al, 2013); early childhood nutrition and parenting intervention (Agustina et al, 2018); avoidance of contaminated objects (Conrad et al, 2020); mental state references (Farkas et al, 2020); self-awareness (Rahimah & Izzaty, 2018); culturally valued qualities and behaviours related to achievement (Suprawati et al, 2014); formation of identities (Watson et al, 2015); disasters (Damayanti et al, 2020); and even road safety (Ahmad et al, 2018). Hartling et al (2010) identified the challenges in making stories which include keeping the authenticity of the story against being evidence-based, addressing consumers' use of the web as the source of health information and striking a balance between being concise, comprehensive and widely applicable, taking into account story length, reading level, narrative mode, depiction of various demographics and exposures to the disease, illustrations and layout.…”
Section: Related Researchmentioning
confidence: 99%